PENINGKATAN KOMPETENSI GURU MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PEMBELAJARAN DI SEKOLAH DASAR MELALUI SUPERVISI KLINIS - Umardulis Umardulis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the demands of an era full of technology so that the learning process must shift from conventional learning to active learning that utilizes ICT in the learning process. The facts found in the field indicate that teachers do not use ICT in the learning process for difficult reasons, teachers do not have the competence to use ICT, and facilities that are less available. The purpose of this study is to improve teacher competence using information and communication technology in learning through clinical supervision. This research is a classroom action research which includes the stages of planning, implementation, observation, and reflection. This research was carried out in the target schools of Pasir Penyu sub-district starting March 13 to April 30 2019 against 10 elementary school teachers. Data analysis using observation sheets that observe the actions of teachers using ICT in the learning process. The results showed an increase in teacher competency using ICT in the learning process with the percentage of the first cycle amounting to 57% with the medium category being 83% which included a very high category. Based on the results and discussion it can be concluded that the implementation of clinical supervision can help the teacher's problems in the use of ICT in the learning process.